Failure of Standard Duplex Stainless Steel X2CrNiMoN22-5-3 under Corrosion Fatigue in Geothermal Environment. Issue 1 (July 2020) - Wolf, Marcus; Pfennig, Anja
Abstract: Corrosion fatigue is well known to lower the lifetime expectancy of high alloyed steels. Duplex stainless steel X2CrNiMoN22-5-3 is a promising candidate to withstand both, corrosion and mechanical stress. Therefore, the corrosion fatigue (CF) was investigated in the Northern German Basin electrolyte at 369 K using a specifically designed corrosion chamber. CF damage was clearly related to lateral grain attack within corrosion pit cavities located perpendicular to the load applied. Additionally, multiple fatigue cracks and preferable deterioration of austenitic phase and intact ferritic phase. A delta-like micro crack structure and a curved path characterizes crack termination with little to no base metal deterioration. Crack initiation may be due to early pit formation resulting in depassivation but also due to local depassivation then resulting in pit formation–both initiation mechanisms lead to crack propagation and early failure.